Marketing Strategies of Travel and Tourism Industry - Varsha Ganatra; A.A. Gde Satia Utama; Purvika Pawar; Sahil Verma; Rudresh Pandey; Jhonathan Whiryawan; Liem Gai Sin; Chong Chiew Ling; Daisy Mui Hung Kee; Chai Yeong Jin; Tan Hui Min; Lim Sin Chen (AIBPM Publisher, 2021)
Travel and Tourism is an assemblage of all the leisure, luxuries, comfort, travel products, and services provided by suppliers including airlines, hotels, transportation like self-drive agencies, cruise lines, restaurants, etc. All these functions require marketing. This study aims to explore the marketing patterns of tourist agencies to increase customer awareness. The tourism sector also helps to promote the various hotels, restaurants, rental agencies by giving a platform for all these services to promote their services and also provide a customer discount for customer satisfaction.